The Use of Digital Storytelling in Teaching English Narrative Texts to Students of Al-Falah Beringin Tambelangan Junior High School - Halima Badria; Febria Cahyani (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to describe the use of digital storytelling in teaching English narrative texts to students of SMPS Al-Falah Beringin Tambelangan using a qualitative descriptive approach. The focus includes the learning process, development of vocabulary and listening comprehension, improvement of speaking confidence, and student and teacher responses to story-based digital media. Data were collected through classroom observations, student and teacher interviews, and documentation such as activity photos, worksheets, story scripts, storyboards, and digital storytelling products. Data analysis was conducted through data reduction, data display, conclusion drawing, and triangulation techniques. The findings reveal that digital storytelling helps students who initially face limited vocabulary, difficulty in understanding oral narratives, and low confidence in using English. Through stages of model reading, drafting, storyboarding, voice recording, pronunciation revision, and presentation, students experience more concrete, collaborative, and meaningful narrative learning. Interview results also show that this strategy supports teachers in integrating narrative text structure with language production practice, although it requires proper time management, resources, and guidance. The study concludes that digital storytelling is a relevant alternative for improving students’ English skills in narrative text learning when implemented gradually and accompanied by process and product assessment.